Can Rabies Be Eradicated? - Rupprecht, C.E.; Barrett, J.; Briggs, D.; Cliquet, F.; Fooks, A.R.; Lumlertdacha, B.; Meslin, F.X.; Müller, Thomas; Nel, L.H.; Schneider, C.; Tordo, N.; Wandeler, A.I. (2013)
Rabies, an acute progressive encephalitis, is an ancient zoonosis. Its distribution encompasses all continents, except Antarctica. Agents consist of at least 11 species orgenotypes of rhabdoviruses, in the Genus Lyssavirus. Susceptible natural hosts include all mammals. Primary reservoirs reside in the Orders Carnivora and Chiroptera. A plethora of variants, maintained by a diversity of abundant hosts, presents a challenge to a strict concept of true eradication. Globally, the domestic dog remains the most significant species for viral transmission, responsible for millions of suspect human exposures and tens of thousands of fatalities. As such, this single major target provides an ideal opportunity for focused intervention programmes in humane disease prevention and control, driven by laboratory-based surveillance and guided via modern epidemiological insights. Historically, substantial technical progress throughout the 20th century led to the development of safe, affordable and efficacious animal and human vaccines, resulting in declining disease burdens in selected developed and developing countries. Regional and local disease resurgence occurs, due in part to a combination of political and economic instability, environmental perturbations, and shifting government priorities. Society must recall that despite the recent recognition of other important emerging infectious diseases, none exceed the case fatality rate of rabies. Given the clear relevance of rabies in public health, agriculture, and conservation biology, substantive international progress must continue towards enhanced public awareness, human rabies prevention, wildlife rabies control, and canine rabies elimination, with renewed collaborative vigour.